"Green lease" and "surveying" cincretism in the formation of the devilopers management system of construction enterprises - Ivakhnenko, I.; Klymchuk, М. (Ways to Improve Construction Efficiency, 2018)
The article is devoted to the process of synthesizing the concepts of "Green Lease" and "Surveying" in shaping the strategy of energy saving management at construction enterprises. As a result of the system analysis, it is proposed to study the strategy of energy saving management of the construction company as part of the energy strategy of the region. The economic-functional method of implementation of the energy saving management strategy for construction enterprises is incorporated, where the structure of the regional energy saving strategy is scientifically substantiated, taking into account the expediency of its integration into integrated strategies of socio-economic development of the region.